Inovações tecnológicas e organizacionais: um estudo de caso dos impactos sobre o trabalho, a produtividade e os custos de produção - Koshaka, Marcos Henrique (2002)
The rapid advance in the process of diffusion of innovations has brought about profound changes in the sphere of production. However, there is no general consensus, and there is still a lot of room for discussion about exactly what are the impacts caused by these innovations, whether for competitiveness between companies and for workers. This dissertation has as main objective to analyze the impacts of technological innovations and organizational innovations at the firm level, observed on the factory floor of a continuous flow process plant, from the early 1990s to the present time, with respect to the evolution of productivity, reduction of variable costs and changes in the qualification requirements of the labor force. It is a case study of a multinational company, leader of the Brazilian market in its segment, producer of non-durable consumer goods. The structure of this dissertation includes three chapters. Chapter 1 consists of an examination of the most relevant issues regarding the adoption of technological innovations, their generation and their diffusion process, as well as the properties and regularities of technical progress, the focus of the so-called neo-Schumpeterian approach. The bibliographic review of this chapter aims to provide a theoretical framework for the case study proposed in this dissertation, leading to an understanding of the most relevant issues regarding the adoption of technological innovations. Chapter 2 deals with the discussion and analysis of the characteristics and trends of the productive restructuring process and its effects on the productive organization, starting in the 1980s, examining its impacts on the dissemination of new forms of production organization and the new qualification profiles . The last chapter, which concerns the main object of this dissertation, discusses the changes adopted by the case study company after the introduction of technological innovations, and seeks a quantitative and qualitative assessment of the impacts of the technological innovations and organizational innovations adopted, regarding the evolution of productivity and the reduction of variable costs, and the new qualification profile required of the workforce.